2018
DOI: 10.1159/000489962
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid as a Predictor of Immunoglobulin A Nephropathy Progression: A Cohort Study of 1965 Cases

Abstract: Background: The role of serum uric acid (SUA) level in the progression of Immunoglobulin A nephropathy (IgAN) remains controversial. Methods: In a cohort of 1,965 cases with biopsy-proven IgAN, we examined the associations of SUA concentration with the primary outcome of a composite of all-cause mortality or kidney failure (defined as a reduction of estimated glomerular filtration rate [eGFR] by 40% from baseline, requirements for dialysis and transplantation), or the outcome of kidney failure alone, assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…With the increase in life expectancy and the large number of diabetic patients, diabetes has replaced chronic glomerulonephritis as the primary cause of new dialysis patients in Shanghai [7] and Beijing [12] which are the big cities in China although the control of blood glucose, blood lipids, and blood pressure [1315] has been strengthened. Recently, studies have shown that a significant proportion of diabetes with normoalbuminuria have glomerular filtration rate (GFR) decrease [8, 16] while serum uric acid (SUA) has reentered the spotlight as a cause of renal insufficiency [17, 18].…”
Section: Discussionmentioning
confidence: 99%
“…With the increase in life expectancy and the large number of diabetic patients, diabetes has replaced chronic glomerulonephritis as the primary cause of new dialysis patients in Shanghai [7] and Beijing [12] which are the big cities in China although the control of blood glucose, blood lipids, and blood pressure [1315] has been strengthened. Recently, studies have shown that a significant proportion of diabetes with normoalbuminuria have glomerular filtration rate (GFR) decrease [8, 16] while serum uric acid (SUA) has reentered the spotlight as a cause of renal insufficiency [17, 18].…”
Section: Discussionmentioning
confidence: 99%
“…This study also has shown that, except for glomerulosclerosis percentage, there is no significant difference in the 2009 Oxford classification, crescentic percentage, and focal segmental sclerosis between the hyperuricemia group and the normo-uricemia group (Moriyama et al, 2015). Another study suggested that the relationship between hyperuricemia and IgAN progression was not very significant in patients with older age, lower eGFR, or interstitial lesion (Zhu et al, 2018). Similarly, this study did not use the updated Oxford classification of IgAN.…”
Section: Introductionmentioning
confidence: 68%
“…Uric acid internalization by URAT 1 is necessary for its deleterious and pro-apoptotic effect at the tubular level, and this is confirmed by the protective effect showed by losartan, which reduced TLR4, MCP1 and Nox4 expression [ 74 ]. Taken together with the association between increased serum uric acid levels and the more severe tubular atrophy and vascular damage described in different series of renal biopsy [ 75 , 76 , 77 , 78 , 79 , 80 ], these findings might explain, at least in part, the unfavorable renal outcomes related to hyperuricemia.…”
Section: Renal Damagementioning
confidence: 74%